ENSURING GEODETIC MONITORING OF LANDSLIDES TO PREVENT EMERGENCY RISKS - Bulysheva Д.; Leonidova І.; Malashchuk О.; Varfolomeieva О.; Panasiuk О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The research is aimed at substantiating the need for geodetic monitoring of landslides and diagnosing methods of high-precision observations and identifying landslides, and giving proposals about the features and conditions of the further observations along the Black Sea coast to prevent emergency risks. In the course of the research, the characteristics of the territory of the Black Sea coastal strip in Odesa region were determined and described. It was found that this territory is characterized by high complexity of engineering and geological conditions and a landslide zone 100-200 m wide was formed along the sea coast. The dangers of landslides in the relevant areas have been identified with consideration of climate change and local features. To carry out geodetic monitoring of landslide processes, 33 geodetic ground rappers and 53 rappers were laid on the shore fortification structure. The coordinates of the rappers were determined using modern geodetic GNSS equipment. The Bernese GNSS Software was used to process the observations. The used methodology and system of landslide slope observations provided reliable and sufficiently complete information for the preparation of a reasonable conclusion about the current state of the landslide, the nature and direction of its movement, as well as the forecast of its conditions for the near future. The analysis of geodetic monitoring of the effectiveness of anti-landslide measures to protect the slope of environmental risk prevention was made. According to the results of the monitoring, the parameters of displacements of soil benchmarks and geodetic landmarks on the grid of the shore protection structure of the slope in space and time were determined. The maximum deviation during the observation period for geodetic ground rappers was 16.52 m, the maximum deviation on the shore fortification structure was 1.02 m. The relevant data is used to ensure the direction of further work on preventing landslides and risks.